TYPES OF FORMATIVE AND SUMMATIVE ASSESSMENT - Rakhmanova Shakhnoza Amrullayevna (Journals Park Publishing, 2023)
Appraisal is a vital piece of any instructive program, it helps in assessing the ideas advanced by understudies in the study hall. Educators ought to utilize such appraisal strategies and procedures that permit them to assess the subject, yet additionally the meta-subject aftereffects of understudies at different phases of the instructive interaction.
Keywords: formative assessment, summative assessment, meta-subject skills, evaluation.